Effects of aerobic exercise on cognitive function and quality of life in patients with Alzheimer’s disease: a systematic review and meta-analysis - Linlin Yang; Zhichao Yuan; Chenggen Peng (BMJ Open)
Objectives Numerous studies have examined the effects of physical activity on cognitive performance and executive function in people with Alzheimer’s disease (AD), although the findings are not entirely consistent. There are also insufficient study reviews for specific workout and assessment tool types. Therefore, the purpose of this study was to systematically investigate the effects of aerobic exercise on the quality of life, cognitive performance and depressive symptoms in people with AD.Design Risk of bias was assessed using the Cochrane risk of bias tool, systematic reviews and meta-analyses using random-effects modelling, and certainty of evidence using the Grading of Recommendations Assessment, Development and Evaluation tool.Data sources PubMed, Web of Science, Cochrane Library, EMBASE, Scopus, CINAHL and CNKI through 12 March 2024.Eligibility criteria The analysis includes all randomised controlled trials (RCTs) that used aerobic exercise as an intervention for individuals with AD.Data extraction and synthesis Two writers selected and searched for data using defined techniques. To investigate possible sources of heterogeneity between studies, meta-regression was carried out using Stata MP V.18.0 and V.14.0 software, standardised mean differences (SMDs) and 95% CIs were computed, and data were reviewed using Review Manager V.5.4 software, which was made available by the Cochrane Collaboration. Sensitivity analyses were employed to ascertain the stability and reliability of the results, and funnel plots and Egger’s test were employed to check for publication bias. Correction and assessment of publication bias was done using Duval and Tweedie clipping methods.Results Aerobic exercise enhanced cognitive function. For the Minimum Mental State Examination (MMSE) (SMD=0.95, 95% CI 0.58 to 1.32, Z=5.06, p<0.00001), Alzheimer’s Disease Assessment Scale-Cognitive Section (ADAS-cog) (SMD=−0.67, 95% CI −1.15 to –0.2, Z=2.77, p=0.006) and quality of life (SMD=0.36, 95% CI 0.08 to 0.64, Z=2.51, p=0.01), but not statistically significant for depressive symptoms (SMD=−0.25, 95% CI −0.63 to 0.13, Z=1.27, p=0.21). Subgroup analysis showed that duration greater than 16 weeks and less than 50 min per intervention improved MMSE Scores. Duration greater than 16 weeks and more than 30 min per intervention improved ADAS-cog Scores in patients with AD. Aerobic exercise greater than 16 weeks, with more than three interventions per week and 30–50 min per intervention improves quality of life in patients with AD.Conclusion The study revealed that aerobic exercise was conducive to the improvement of cognitive function and quality of life among patients with AD, yet it did not exert a significant impact on the amelioration of depressive symptoms. Nevertheless, given the high level of heterogeneity and the variations in the quality of the included studies, the conclusions require further verification through more scientifically objective RCTs.PROSPERO registration number CRD42024526067